2013
DOI: 10.4172/2155-6156.1000257
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Yoga and Aerobic Exercises in Obesity and its Effect on Pulmonary Function

Abstract: Citation: Shinde N, Shinde KJ, Khatri SM, Hande D (2013) A Comparative Study of Yoga and Aerobic Exercises in Obesity and its Effect on Pulmonary Function. J Diabetes Metab 4: 257.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…Exercises such as walking, exercise walking, mountain climbing, and international standard dancing, were not significantly associated with a change in obesity measures, but these 4 kinds of exercise could blunt the genetic effects on BMI. By comparing rows of “walking” and “yoga” in S8–S10 Tables, our result is consistent with a previous finding that engaging in yoga shows a larger reduction in BMI than walking [61].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Exercises such as walking, exercise walking, mountain climbing, and international standard dancing, were not significantly associated with a change in obesity measures, but these 4 kinds of exercise could blunt the genetic effects on BMI. By comparing rows of “walking” and “yoga” in S8–S10 Tables, our result is consistent with a previous finding that engaging in yoga shows a larger reduction in BMI than walking [61].…”
Section: Discussionsupporting
confidence: 90%
“…Some previous studies investigated the efficacy of performing several kinds of exercise in preventing obesity [60, 61]. For example, a randomized controlled trial with 64 subjects assigned to the Tai Chi group and 78 assigned to the control group demonstrated that performing Tai Chi led to a marked but non-significant reduction in WC [60].…”
Section: Discussionmentioning
confidence: 99%
“…the efficacy of another drug which acts as an insulin lowering agent named metformin, in reducing breast cancer recurrence is presently being studied extensively [101,102,103]. Simultaneously in the recent years Yoga based lifestyle interventions that is a form of physical activity facilitating in accomplishing recommended levels of physical fitness have gained much attention and are found to effectively thwart and hinder the progression of cardiovascular and metabolic syndromes like that of obesity [104,105]. The method of action of such benefit may be credited to a reduction in weight and stress, networking at mind and body levels, thereby leading to a decline in inflammation, and causation and progression of the disease [106].…”
Section: Discussionmentioning
confidence: 99%
“…It provides qualitatively different exercise experience which may be perceived as less strenuous and more pleasurable. 3 In general, Medical students experience more stress than the general population. This may be due to workload they face in their academic sessions.…”
Section: Introductionmentioning
confidence: 99%